Character Education in Building Life Skills /Pendidikan Karakter dalam Membangun Kecakapan Hidup - Umi Salamah; Kasuwi Saiban; Triyo Supriyatno; Sa'dun Akbar (Al-Mudarris: Journal Of Education, 2022)
The research focused on the implementation of character building to improve students’ life skills and the implication of character building on students’ life skills in PPBM. It was carried out using a qualitative approach and case study design in business units of PPBM. The data source of the research consisted of the caretakers, teachers, the head of the vocational training center, and students involved in the management, work, and training in various business units. The researcher collected the data using observation, interviews, open questionnaires, and documentation. The key instrument of the research is the researcher herself. However, the researcher employed research instruments of observation, interview, and open questionnaire to help her during the process. The data was analyzed using description, condensation, categorization, and interpretation processes.The result of the research shows that (1) to improve students’ life skills, character building is carried out by understanding the vision, mission, and objectives of the Islamic boarding school. The learning starts from the production of goods and services using sources and learning media in an extensive way (involving tutors and professionals of certain business unit), internship, independent learning using internet (Youtube, WA, Instagram, and other social media), the practice of management, work, and training in the business units, assessment, and authentic evaluation by involving students in the management and work of business unit; the learning monitoring is done by report and reflection on their performance in each business unit; (2) The implication of character building on students’ life skills includes the developing of students’ individual skill, awareness to live independent, religious competence (praying attitude, being grateful and patient, being responsible, struggling, and serious in work); social competence, namely the competence to communicate, collaborate, and cooperate; academic competence; and vocational competence, namely the competence to work in business unit experienced by students in PPBM.